Da proteção do trabalhador migrante ao telemigrante no Brasil a partir da normativa internacional - Loch, Flávio (2021)
Study that investigates the protection of the rights of migrant workers, especially telemigrants in Brazil, in light of the international normative framework, around the following issue: what protection is attributed to migrant workers in Brazil, especially telemigrants, in light of the international normative framework and national legislation? In general, the objective is to analyze the protection of the rights of migrant workers in Brazil, especially telemigrants, in light of the international regulatory framework and national legislation. In unfolding this purpose, the aim is also to: analyze the characteristics of labor migration, including the theoretical foundations related to migrant workers, especially telemigrants; analyze the international regulatory framework regarding the protection of migrant workers, especially telemigrants; verify the application of international standards and the Brazilian regulatory framework regarding the protection of migrant workers, especially the protection of telemigrants. The study was developed through bibliographical and documentary research, based on the exploration of the doctrine elaborated on the topic and the identification of legal provisions of International Law and Domestic Law applicable to the proposed legal problem. The conclusions point to the importance of ratification of the International Convention on migrant workers and their family members by Brazil, and to the need to adapt the CLT to the referenced norms of International Law, especially with regard to the two-thirds norm which, as is evident, it is discriminatory and exclusionary. It also emerges from the reflections presented that the provisions that deal with teleworking are treated in a broader and less repressible way when establishing the guarantees for teleworkers and telemigrants, hindered by the exclusion of the working day and the possibility of changing the telematic work regime. for the face-to-face regime.